Estudo sobre uso de novos citrandarins como porta-enxertos para laranja pera - Moretto, Rafael Kupper (Universidade Federal de São Carlos, 2019)
Currently, the most of the citrus plants in the Brazil are on the rootstocks Rangpur lime and Swingle citrumelo, which may put at risk the Brazilian citriculture by the use of few genotypes. The use of other rootstocks such as Poncirus trifoliata is limited due to the occurrence of incompatibility between selections of this rootstock and Pera sweet orange, in addition to the susceptibility to drought. Therefore, the use of citrandarins [Sunki mandarin (Citrus sunki Hort. Ex Tan.) X Poncirus trifoliata (L.) Raf.] constitute a new generation of rootstocks, which present potential as an alternative to the use of Rangpur lime, enabling the formation of long-lived plants and conferring to the canopy production and quality of satisfactory fruits. In view of the above, the present work had the objective of evaluating the development of Pera sweet orange plants, regarding their vegetative development; physical and chemical characteristics of the fruits; to phenology and compatibility, when grafted on different varieties and rootstock hybrids, in two different edaphoclimatic conditions. The experiments are established in two municipalities of the State of São Paulo, Gavião Peixoto and Barretos and, in a randomized blocks statistical design. The data obtained in this study showed that the production of orange Pera on the citrandarins in the region of Gavião Peixoto, was 15% larger than in the Barretos region. It can be observed that the different edaphoclimatic conditions presented in the two regions influenced the behavior of rootstocks regarding fruit fixation and yield, and that the most important rootstock was citrandarin128.
Study of new citrandarins as rootstocks to pera sweet orange
Keywords: Melhoramento; Híbridos; Citros; Enhancement; Hybrids; Citrus; CIENCIAS AGRARIAS::AGRONOMIA